The Role of Leadership in Decision Making at The Baitul Muslimin Mosque, Kebonagung Village, Kec. Sukodono, Kab. Sidoarjo - Viqi Al Wahyuddin; Ahmad Khairul Hakim (Proceedings of International Conference on Da'wa and Communication, 2020)
This study aims to determine the role of leadership in decision making at the Baitul Muslimin Mosque. In addition, also to find out the decision-making process in the Baitul Muslimin Mosque. The method used in this study is a qualitative descriptive method. The descriptive method is used as a practical way to describe and explain the role of leadership in decision making. Then, the data collection technique used data triangulation. This method is done by observation, documentation, and interviews. The results of this study are the leader at the Baitul Muslimin Mosque is a democratic person. This can be seen from the way decisions are made by deliberation and are happy to accommodate the aspirations of members. The role of the leader at the Baitul Muslimin Mosque is to direct, guide, accommodate aspirations, mediate if there are differences of opinion, and provide motivation. Then, the role of the leader at the Baitul Muslimin Mosque in decision making, namely mediating if there are differences of opinion, moderating, accommodating aspirations, and holding a vote to make the best decision. The stages of decision making at the Baitul Muslimin Mosque, namely: Search (this stage makes invitations and deliberation), Design (this stage mediates differences of opinion and makes alternative problems), Choice (this stage chooses the alternatives that have been made), Implementation (this stage carries out decisions that have been determined).